When I Raised My Eyes Again: Women’s Journey to gain Power In Sidhwa’s Ice-Candy Man - Wahla, Mahin; Mamona, Mamona (Journal of English Language and Literature (ISSN: 2368-2132), 2017)
The aim of the present study is to show the women’s journey to gain power in Bapsi Sidhwa’s novel Ice-Candy Man. This will be done by showing their dual representation in the novel in the light of Feminist Theory. The study will first show how the women are victims of patriarchal oppression, subjugation, marginalization and sexual exploitation in the novel, and then it will be described that how they are not entirely victim. This will be done by showing their strength to come out of that situation of victimization to gain power and assert their independent identity.